A new species of Acrotaeniostola Hendel and new records of Gastrozonini and Ceratitidini (Diptera: Tephritidae) from India - David, K. J.; Sachin, K.; Hancock, D. L. (Zootaxa, 2020)
A new species of Acrotaeniostola Hendel, A. connexa sp. n. of tribe Gastrozonini, is described from India. Acroceratitis incompleta Hardy of tribe Gastrozonini and Ceratitella sobrina (Zia) of tribe Ceratitidini have been recorded for the first time from India. The genus Ceratitella Malloch and tribe Ceratitidini are recorded for the first time from India.